How to Limit the Spillover from an Inflation Surge to Inflation Expectations? - Lena Dräger; Michael J. Lamla; Damjan Pfajfar (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study the effects of forward-looking communication in an environment of rising inflation rates on German consumers' inflation expectations using a randomized control trial. We show that information about rising inflation increases short- and long-term inflation expectations. This initial increase in expectations can be mitigated using forward-looking information about inflation. Among these information treatments, professional forecasters' projections seem to reduce inflation expectations by more than policymaker's characterization of inflation as a temporary phenomenon.
Keywords: E31; E52; E58; D84; 330; short-run and long-run inflation expectations; inflation surge; randomized control trial; survey experiment; persistent or transitory inflation shock